Penentuan Rute Potensial Sarana Angkutan Umum Massal (SAUM) Berbasis Analisis Sistem Informasi Geografis di Kawasan Perkotaan Mamminasata - Ahmad Aulia Bahrun Amieq; Ananto Yudono; Arifuddin Akil (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2017)
Mamminasata has been served by the Public Mass Transportation Facility (PMTF) in the form of BRT, but the development of the route has not yet represented the demands of the community, because 70% of people choose to use private vehicles in their activities. This study aims to identify the determinants of PMTF's potential routes, identify the distribution of activity centers and determine the corridors of potential PMTF routes in Mamminasata. Primary data were obtained through field observations and origin-destination surveys, while secondary data were obtained through NSPM, literature, previous research and related agencies. The analysis technique uses origin-destination matrix, spearman correlation, and analysis based on Geographic Information Systems (GIS) namely kernel density, desire line, and network analyst. The results of this study indicate that the factors that correlate significantly with the intensity of the route are trip generation, attraction, and purpose of travel. The trend of movement patterns shows the central government offices, economy and business, education, shopping and entertainment, recreation, and settlements. There are 41 dominant road sections serving trips in Mamminasata. The road network is divided into five potential route priorities, with six road sections being the first priority. Thus found 9 SAUM corridors that serve the movement from the center of the settlement to the center of other activities (corridors 1, 2, 4, 6, 9), the commuter movement from the surrounding districts to the core city (corridors 3, 7, 8) and serve the movement connecting activity centers in the downtown area (corridor 5).